Adsorption Ability of Bagasse Lignin (LB), Bagasse Lignin Carbon (LBF), and Amination Lignin (LA) for Chrome (III) - Berghuis, Nila Tanyela; Novianti, Nurul Fitri; Ratri, Paramita Jaya (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
Analyzing the Cr(III) adsorption properties of bagasse lignin (LB), bagasse lignin carbon (LBF), and lignin amine (LA). Variable adsorption studies were performed, including variations in mass, contact time, and pH. The adsorption ability test was carried out first by varying the mass of the adsorbent to determine the optimum mass of each adsorbent LB, LBF, and LA for the Cr(III) adsorbate. The ability of lignin adsorbents (LB, LBF, and LA) to adsorb Cr(III) was optimum at 0.015 g adsorbent mass contact time of 90 minutes, and the adsorbate solution had a pH of 6. The adsorption capacity (Qm) value for bagasse lignin adsorbent (LB) was 8.6050 mg/g at 30°C, bagasse carbon lignin (LBF) was 9.8717 mg/g (30°C), and ammine lignin (LA) with the highest value is 9.9800 mg/g (35 °C).